Beyond Hierarchy: A Systematic Review of Organizational Transformation Through Agile, Network and Platform-Based Models - Munawaroh Munawaroh; Dewi Irianti; Fanny Satya Utama; Herdiansyah Herdiansyah; Siti Saroh (International Journal of Science and Environment (IJSE), 2026)
Traditional hierarchical organizations prove increasingly inadequate confronting volatile, uncertain, complex, and ambiguous (VUCA) environments necessitating radical structural transformation toward agile, network, and platform-based models.This systematic literature review synthesizes empirical evidence examining transformation pathways, implementation challenges, and performance outcomes across these three organizational archetypes. Following rigorous review protocols, comprehensive search across academic databases yielded 24 peer-reviewed publications (2015-2025) subjected to thematic analysis.Findings reveal three critical themes: agile principles enabling rapid adaptation through iterative processes and self-organizing teams, network structures facilitating cross-boundary collaboration through decentralized decision-making, and platform ecosystems leveraging digital infrastructure for value co-creation.Literature demonstrates significant gap regarding systematic integration frameworks connecting these complementary models organizations typically adopt piecemeal approaches missing synergistic potential. Research contributes novel Agile-Network-Platform (ANP) Integration Framework proposing three-layer architecture: operational agility (team level),network coordination (organizational level), and platform orchestration (ecosystem level).Organizations should implement parallel transformation addressing team empowerment, structural flattening, and digital platform development creating adaptive organizational systems balancing flexibility, collaboration, and scalability. Study limitations include literature review methodology and emphasis on technology-intensive industries suggesting comparative research across sectors and longitudinal implementations examining ANP framework effectiveness over transformation journeys.